Compact Operators for Almost Conservative and Strongly Conservative Matrices - S. A. Mohiuddine; M. Mursaleen; A. Alotaibi (Abstract and Applied Analysis)
We obtain the necessary and sufficient conditions for an almost conservative matrix to define a compact operator. We also establish some necessary and sufficient (or only sufficient) conditions for operators to be compact for matrix classes (f,X), where X=c,c0,l∞. These results are achieved by applying the Hausdorff measure of noncompactness.